Cytotoxicity Test of Cocoa Leaf Ethanol Extract (Theobroma Cacao L.) With Brine Shrimp Lethality Test (BSLT) Method - Zulmai Rani; Ridwanto Ridwanto; Dikki Miswanda; Rafita Yuniarti; Ani Sutiani; Ricky Andi Syahputra; Reza Irma (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Cancer is a disease characterized by uncontrolled cell division and the ability of these cells to invade other biological tissues, either by direct growth in adjacent tissues or by migration of cells to distant sites. The purpose of this study was to determine the class of secondary metabolites contained in the ethanol extract of cocoa leaves and their cytotoxicity by looking at the LC50 value using the Brine Shrimp Lethality Test (BSLT) method. This research includes phytochemical screening of ethanol extract and the BSLT method by looking at the number of deaths of Artemia salina leach larvae (LC50). The results of phytochemical screening tests showed that the cocoa leaves contained flavonoids, alkaloids, tannins, saponins, steroids, and glycosides. The cytotoxicity test with probit analysis showed an LC50 value of 269,15 µg/mL, so it was concluded that the ethanol extract of cocoa leaves was toxic and had potential as an anticancer.